Light-weight, high-gain antenna with broad temperature adaptability based on multifunctional 3D woven spacer Kevlar/polyimide composites. (February 2022) - Zhang, Kun; Zheng, Liangang; Pei, Rui; Chen, Long; Xu, Fujun
Abstract: Multifunctional composites endowed with signal transmission and excellent mechanical properties show promising applications in aviation and aerospace. In this study, in combination with copper yarn, Kevlar yarn and polyimide resin, a light-weight 3D woven spacer composite antenna (3DWSCA) was developed for effective wireless signal transmitting. Based on the advanced 3D structural design, the Kevlar/Polyimide composite substrate with high specific strength (11.2 MPa/g·cm −3 ), ultra-low density (0.34 g/cm 3 ), superb dielectric properties and small temperature coefficient of resonant frequency (TCF: -12.6 ppm/°C) was constructed. Accordingly, the 3DWSCA realized a gain value of 4.95 dB near designed frequency (2.34 GHz) with a good impedance matching (S11 value < −25 dB). Moreover, the 3DWSCA demonstrated broad temperature adaptability, maintaining stable resonance frequency and radiation properties in the temperature range of −160–200 °C. With these excellent performances, 3DWSCAs can be integrated into the component structure of high-velocity aircrafts to operate in a wide range of temperature, without sacrificing their mechanical and signal transmission functions. Graphical abstract: Image 1 Highlights: A novel 3D spacer integrated multifunctional composite antenna is proposed. The electromagnetic properties were verified by simulation and experimental methods. It showed superb mechanical (11.2 MPa/g·cm −3 ) and radiation properties (4.95 dB). The ultralow density (0.34 g/cm 3 ) is essential for the aerospace applications. Its unique structure cause superb temperature adaptability in range of −160–200 °C.